2013
DOI: 10.1111/j.1600-0706.2013.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Go with the flow: water velocity regulates herbivore foraging decisions in river catchments

Abstract: Daunt, Francis; O'Hare, Matthew T.. 2013. Go with the flow: water velocity regulates herbivore foraging decisions in river catchments. Oikos, 122 (12). 1720-1729. 10.1111/j.1600-0706.2013.00592.x Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
(65 reference statements)
1
28
0
Order By: Relevance
“…This assumption is likely to be true very generally (Bautista, Tinbergen, & Kacelnik, 2001;Bautista, Tinbergen, Wiersma, & Kacelnik, 1998;Berger & Gotthard, 2008;Cooper & Sherbrooke, 2013;Helfman & Winkelman, 1991;Lourdais et al, 2014;Williams & Yeates, 2004;Wood, Stillman, Wheeler, Groves, Hambly, et al, 2013). (3) Optimal foraging theory is based on the concept of natural selection as a fitnessmaximizing algorithm, where fitness is assumed to depend on the dominant costs and benefits associated with behavioural options.…”
mentioning
confidence: 99%
“…This assumption is likely to be true very generally (Bautista, Tinbergen, & Kacelnik, 2001;Bautista, Tinbergen, Wiersma, & Kacelnik, 1998;Berger & Gotthard, 2008;Cooper & Sherbrooke, 2013;Helfman & Winkelman, 1991;Lourdais et al, 2014;Williams & Yeates, 2004;Wood, Stillman, Wheeler, Groves, Hambly, et al, 2013). (3) Optimal foraging theory is based on the concept of natural selection as a fitnessmaximizing algorithm, where fitness is assumed to depend on the dominant costs and benefits associated with behavioural options.…”
mentioning
confidence: 99%
“…In comparison, for Whooper Swans (Cygnus cygnus) the most important activity was feeding, while only 28% of their day was spent swimming (Black and Rees 1984). Swimming is an energetically expensive activity for Mute Swans and the key factor influencing the behavioral decision to switch between terrestrial and aquatic feeding habitats (Wood et al 2013). Therefore, using wind for transportation may have impact on the daily energy spent.…”
Section: Discussionmentioning
confidence: 99%
“…If the Mute Swan would have been swimming at the same speed, the energetic cost would have been~12 times the basal metabolic rate (BMR). This figure is based on the energetic cost of swimming in Mute Swans as developed by Wood et al (2013) where the cost of swimming (in W) is equal to 314.9 v 2 À 87.2 v þ 59.0 (v velocity in m/s). For the speed 1.3 m/s, the energy is thus 477.8 W, which with a BMR of 39 W (as calculated by Wood et al 2013) is 12.25 times the BMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grazing by flocks of swans affects <0.5 km reaches of river, and only affects a minority of river sites, typically for short periods (<6 weeks) before the flock moves on [44]. Previous research has shown that this pattern of swan habitat selection is determined by changes in the relative profitability of different feeding areas within the landscape [47]. Swan grazing damage to river macrophytes is a particular problem between early-May, when the swan flocks enter the river [47], and mid-June when most individuals move to the estuary to moult [45].…”
Section: Introductionmentioning
confidence: 99%